Functional Consequences of Homocysteinylation of the Elastic Fiber Proteins Fibrillin-1 and Tropoelastin - Hubmacher, Dirk (American Society for Biochemistry and Molecular Biology, 2010)
Homocystinuria caused by cystathionine-β-synthase deficiency represents a severe form of homocysteinemias, which generally result in various degrees of elevated plasma homocysteine levels. Marfan syndrome is caused by mutations in fibrillin-1, which is one of the major constituents of connective tissue microfibrils. Despite the fundamentally different origins, both diseases share common clinical symptoms in the connective tissue such as long bone overgrowth, scoliosis, and ectopia lentis, whereas they differ in others. Fibrillin-1 contains ∼13% cysteine residues and can be modified by homocysteine. We report here that homocysteinylation affects functional properties of fibrillin-1 and tropoelastin. We used recombinant fragments spanning the entire fibrillin-1 molecule to demonstrate that homocysteinylation, but not cysteinylation leads to abnormal self-interaction, which was attributed to a reduced amount of multimerization of the fibrillin-1 C terminus. The deposition of the fibrillin-1 network by human dermal fibroblasts was greatly reduced by homocysteine, but not by cysteine. Furthermore, homocysteinylation, but not cysteinylation of elastin-like polypeptides resulted in modified coacervation properties. In summary, the results provide new insights into pathogenetic mechanisms potentially involved in cystathionine-β-synthase-deficient homocystinuria.